Sergei Eisenstein’s System Thinking: Influences and Inspirations - Bulgakowa Oksana (Cultural Science)
In 1932, Sergei Eisenstein started work on his key theoretical book, Grundproblem (later Method), which would present his theoretical system. In the very first notes, he defines a goal that seems to be similar to Aleksandr Bogdanov’s tektology: to find a basic structure – an isomorph – for a work of art but also for the growth of plants and bones, for human society and the organization of bees and ants. Eisenstein’s system thinking was inspired and defined by his basic hypotheses: the structure of an artwork is perceived as a form that equates to multi-layered consciousness in the transition from the pre-logical, sensual to logical thought that the recipient experiences during the ecstatic perception of an artwork. Essential principles of modernist art – fragmentation, montage, visualization and rhythmic recurrence, the object of Eisenstein’s analysis, – determined the new form of Eisenstein’s writing and thinking and revolutionized the theory and the form of its rendition. Eisenstein rejected linear logic and sought forms for a hypertext that in his eyes were closer to associative, spherical and labyrinthine thought structures that to date have found expression only in modernist art experiments.